A Retrospective Analysis of Thymoma: Clinical Radiological Pathological Features and Treatment Modalities – Insights from a Tertiary Care Center - A. Vasudevan; Keerthi Prakash; Ajay Narasimhan; R. Sridhar; R. Narasimhan; C Ganapathy Arumugam (Journal of Association of Pulmonologist of Tamil Nadu)
Background and Objectives: Thymoma is the most common tumor found in the anterior mediastinum, but it is still considered a rare neoplasm, with an incidence rate of 0.13–0.26 cases per 100,000 people each year. This study aimed to analyze the clinical, radiological, and pathological characteristics and treatment modalities of thymoma cases at our institute. Methods: This retrospective observational study was conducted at Apollo Hospital, Chennai, from May 2021 to October 2023. Forty-eight patients with thymoma attended during the above period. Their clinical features, radiological, management, and follow-up, were collected and analyzed. After applying the inclusion and exclusion criteria, 43 patients were included in the study. Results: Thymoma had more incidence in the age group between 30 and 60 years (58.5%). Incidental finding was the most common initial presentation of thymoma in 41.9% of the participants. The majority of participants with paraneoplastic syndromes (71.4%) had myasthenia gravis (MG). Among the 39 operated patients, 3 (7.6%) had robotic surgery, and the recovery (7 days) was faster than conventional surgery. Conclusion: Our study highlights the importance of considering thymoma in patients presenting with anterior mediastinal masses, MG, or incidental findings on imaging. Most thymomas are treatable with minimally invasive techniques, leading to favorable outcomes.